2021
DOI: 10.4103/2221-1691.326098
|View full text |Cite
|
Sign up to set email alerts
|

Gracilaria fisheri oligosaccharides ameliorate inflammation and colonic epithelial barrier dysfunction in mice with acetic acid-induced colitis

Abstract: Objective: To investigate the effect of Gracilaria fisheri oligosaccharides (GFO) on inflammation and colonic epithelial barrier dysfunction in colitis mice. Methods: The animals were treated by oral gavage with distilled water, 1 000 mg/kg inulin, 100, 500, or 1 000 mg/kg GFO for 14 d, or treated with 50 mg/kg mesalamine for 5 d after colitis induction (on day 10). Histopathology, inflammatory cytokines, colonic permeability, and tight junction protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Since shortened colon length is a well-known marker of colitis [19,20], the normal length and histology of the colon seen in this study confirm that Sargassum extract did not cause colon inflammation. Furthermore, the extract did not cause constipation, but in contrast, it increased gut motility and number of goblet cells [5].…”
Section: Discussionsupporting
confidence: 79%
“…Since shortened colon length is a well-known marker of colitis [19,20], the normal length and histology of the colon seen in this study confirm that Sargassum extract did not cause colon inflammation. Furthermore, the extract did not cause constipation, but in contrast, it increased gut motility and number of goblet cells [5].…”
Section: Discussionsupporting
confidence: 79%
“…Transepithelial electrical resistance (TEER) was measured when a current of 3 µA was passed. TEER was calculated according to Ohm’s law ( Siringoringo et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that when APSs were hydrolyzed with β-agarase, the mixture of AOSs was smaller than that of the APSs by half (50.62%), as AOSs with Mn were 1345 Da and Mw were 1756 Da, followed by 49.38% of AOSs with Mn and Mw were 2.215 × 10 4 Da and 2.715 × 10 4 Da, respectively. Siringoringo et al [33] reported that the molecular weight of AOSs (DP1-DP9) from G. fisheri was in the range of 540-1800 Da. In further studies, the activity of several enzymes could be investigated by studying the hydrolytic efficiency of β-agarase together with α-agarase, since these two enzymes exhibit different specificities to glycosidic linkages.…”
Section: Agar Oligosaccharide (Aos) Production and Characterizationmentioning
confidence: 99%